1965
DOI: 10.1126/science.150.3698.893
|View full text |Cite
|
Sign up to set email alerts
|

Bone: Formation by Autoinduction

Abstract: Wandering histiocytes, foreign body giant cells, and inflammatory connective-tissue cells are stimulated by degradation products of dead matrix to grow in and repopulate the area of an implant of decalcified bone. Histiocytes are more numerous than any other cell form and may transfer collagenolytic activity to the substrate to cause dissolution of the matrix. The process is followed immediately by new-bone formation by autoinduction in which both the inductor cells and the induced cells are derived from ingro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
2,309
2
124

Year Published

1981
1981
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 5,060 publications
(2,517 citation statements)
references
References 14 publications
11
2,309
2
124
Order By: Relevance
“…5 Thus far 15 BMPs have been identi®ed and they are all members of the TGF-b superfamily, with the exception of BMP-1. 6 Their osteoinductive ability in vivo has stimulated potential therapeutic applications in reconstructive orthopaedic, periodontal and craniofacial surgery.…”
Section: Bone Morphogenetic Proteinsmentioning
confidence: 99%
“…5 Thus far 15 BMPs have been identi®ed and they are all members of the TGF-b superfamily, with the exception of BMP-1. 6 Their osteoinductive ability in vivo has stimulated potential therapeutic applications in reconstructive orthopaedic, periodontal and craniofacial surgery.…”
Section: Bone Morphogenetic Proteinsmentioning
confidence: 99%
“…BMPs are known to induce bone formation (Urist, 1965;Wosney et al, 1988). BMP7 is one of the main sources of BMPs in limb development (Robert, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In 1965, Marshall Urist [6,47] revolutionized the current understanding of fracture healing by hypothesizing the existence of bone morphogenetic proteins (BMPs) in the extracellular collagenous bone matrix. In 1988, Wozney et al [49] identified the genetic sequences of BMPs.…”
Section: Introductionmentioning
confidence: 99%